The Use of Kahoot for Teaching Vocabulary - Samsuddin Samsuddin; Tambunan Tambunan; Alberth Alberth (Halu Oleo University, 2022)
This research aimed to investigate whether the use of Kahoot! application has a significant effect on students’ vocabulary and whether the students have positive perceptions towards the use of Kahoot! as a media in learning academic vocabulary. This research was conducted with the fourth semester students of the English department of UM Kendari which involved 31 students. The data were attained from students’ vocabulary test and questionnaire. Paired sample ttest indicated that p<0.000, suggesting a significant effect of Kahoot! on students’ vocabulary achievement. The results of the questionnaire suggested that the students have a positive perception of Kahoot! with 75.38% participants favoring its application. With these results, it can be stated that Kahoot! application is able to improve the students’ vocabulary achievement and that students enjoy learning vocabulary using Kahoot! Implications of these findings will be critically discussed in this paper.